PENGARUH BRAND ACTIVATION TERHADAP CUSTOMER ENGAGEMENT (Studi pada Pengikut Instagram @PT.XYZ di Kota Bandung) THE INFLUENCE OF BRAND ACTIVATION ON CUSTOMER ENGAGEMENT (A Study on Instagram Followers of @PT.XYZ Bandung City) - Rachma Wahyu Kusuma Wardhani; Lina Auliana; Zaenal Muttaqin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of brand activation on customer engagement among Instagram followers of @PT.XYZ in Bandung City. PT.XYZ is a local fashion brand specializing in footwear and accessories, with an engagement rate of only 0.09%, significantly below the fashion industry average of 2.3%. A quantitative survey approach was employed, with primary data collected through questionnaires distributed to 100 female respondents aged 19–25 who are active followers of the PT.XYZ Instagram account residing in Bandung. Data were analyzed using validity, reliability, normality, and linearity tests, followed by simple linear regression, correlation coefficient, coefficient of determination, and t-test. The results indicate that brand activation has a positive and significant effect on customer engagement, with a t-test significance value below 0.05. Brand activation scored highest on the sense dimension (89.62%), followed by think (87.62%), act (86.87%), and feel/relate (84.66%), all categorized as excellent. Among customer engagement dimensions, ideas scored highest while reviews scored lowest. These findings imply that improving the quality and interactivity of brand activation activities on social media consistently drives higher customer engagement.